Adding a strategic lens to feasibility analysis - Gregory Berry; Kareem M. Shabana (New England Journal of Entrepreneurship (NEJE), 2020)
Purpose - Traditional feasibility analysis is focused on the immediate and urgent needs of a new venture start-up. All four parts of the feasibility analysis (product/service, industry/market, organizational, and financial) are valuable and essential, but what is missed is a part that provided attention to the longer-term requirements for success and sustainability. A fifth strategic feasibility analysis is needed, focused on the long-term sustainability of the new venture. This strategic/contingent context-dependency lens considers the organization's long-term survival, confirming that organizational success depends on the new venture's ability to emphasize its uniqueness and fit with its external environment. Design/methodology/approach - This paper takes advantage of the decades-long literature review in Strategy to combine known data with entrepreneurial practice in undertaking the feasibility analysis. Findings - This enhanced feasibility analysis adds a strategic lens beyond the traditional four-part feasibility analysis, resulting in identifiable value-added benefits and awareness of potential opportunities or threats in the longer term. Research limitations/implications - This research is conceptual and theoretical at this point, without field implementation. Practical implications - New venture failure is an ongoing concern for many. This suggested strategic lens, especially the sustainability aspect (beyond the "what-do-we-need-to-do-to-open-the-doors" of much feasibility analysis) may prove very useful. Competitive advantage is examined in the traditional feasibility analysis, but this strategic lens suggests a longer term examination, and engages with competitor response. Social implications - If adopted, this enhanced analysis may lead to greater success for new venture start-ups, thus less wasted time, energy and money. Originality/value - This is the first attempt at adding a focused strategic lens to the traditional entrepreneurial feasibility analysis. This may seem like a simple and elementary shift of perspective, but the implications are huge, and take advantage of the decades-long research stream in strategic thinking and planning.
Keywords: 650; Competitive advantage; Feasibility analysis; Strategic analysis; Sustainability